2013
DOI: 10.1371/journal.pone.0070773
|View full text |Cite|
|
Sign up to set email alerts
|

Gadd153 and NF-κB Crosstalk Regulates 27-Hydroxycholesterol-Induced Increase in BACE1 and β-Amyloid Production in Human Neuroblastoma SH-SY5Y Cells

Abstract: β-amyloid (Aβ) peptide, accumulation of which is a culprit for Alzheimer’s disease (AD), is derived from the initial cleavage of amyloid precursor protein by the aspartyl protease BACE1. Identification of cellular mechanisms that regulate BACE1 production is of high relevance to the search for potential disease-modifying therapies that inhibit BACE1 to reduce Aβ accumulation and AD progression. In the present study, we show that the cholesterol oxidation product 27-hydroxycholesterol (27-OHC) increases BACE1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 57 publications
2
61
0
Order By: Relevance
“…Likewise, NF-B acts as a repressor for BACE-1 transcription in differentiated neuronal cells and non-activated glia cells but as an activator in activated astrocytes and the A␤-exposed neuronal cultures (56). In neuroblastoma SH-SY5 cells, NF-B interacts with GADD153 to regulate BACE-1 expression induced by 27-hydroxycholesterol (57). Similarly, YY1 binds to the BACE-1 promoter in PC12 cells and neurons in culture, but in the brain, BACE-1 and YY1 are co-expressed in only a minor population of neurons (58).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, NF-B acts as a repressor for BACE-1 transcription in differentiated neuronal cells and non-activated glia cells but as an activator in activated astrocytes and the A␤-exposed neuronal cultures (56). In neuroblastoma SH-SY5 cells, NF-B interacts with GADD153 to regulate BACE-1 expression induced by 27-hydroxycholesterol (57). Similarly, YY1 binds to the BACE-1 promoter in PC12 cells and neurons in culture, but in the brain, BACE-1 and YY1 are co-expressed in only a minor population of neurons (58).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that ER stress-mediated CHOP activation plays a central role in the triggering of AD pathological hallmarks. We also demonstrated that CHOP and the transcription factor NF-κB work in concert to regulate the transcription of BACE1, the enzyme that initiates the cleavage of the amyloid precursor protein to yield Aβ (Marwarha et al, 2013). We further showed that leptin attenuates the activation and transcriptional activity of NF-κB by reducing the acetylation of the p65 subunit in a SIRT1-dependent manner, thus inhibiting NF-κB-mediated transcription of BACE1 and consequently reducing Amyloid-β genesis.…”
Section: Introductionmentioning
confidence: 89%
“…2). The upregulation of BACE 1 by 27-hydroxycholesterol, an oxidation product of cholesterol, in SHSY5Y cells also requires NF-κB activation as well as the involvement of the gadd153 gene (growth arrest and DNA damage induced gene 153), and in triple transgenic AD mice the deposition of amyloid β peptide is preceded by the increased activity of NF-κB and gadd153 [116].…”
Section: Nf-κb and Alzheimer's Diseasementioning
confidence: 99%